Navigating Metabolic Challenges in Ovarian Cancer: Insights and Innovations in Drug Repurposing - Sara Mikhael; Georges Daoud (Cancer Medicine)
ABSTRACT Background Ovarian cancer (OC) is the most lethal gynecological malignancy and a major global health concern, often diagnosed at advanced stages with poor survival rates. Despite advancements in treatment, resistance to standard chemotherapy remains a critical challenge with limited treatment options available. In recent years, the role of metabolic reprogramming in OC has emerged as a key factor driving tumor progression, therapy resistance, and poor clinical outcomes. Methods This review explores the intricate connections between metabolic syndrome, enhanced glycolysis, and altered lipid metabolism within OC cells, which fuel the aggressive nature of the disease. We discuss how metabolic pathways are rewired in OC to support uncontrolled cell proliferation, survival under hypoxic conditions, and evasion of cell death mechanisms, positioning metabolic alterations as central to disease progression. The review also highlights the potential of repurposed metabolic‐targeting drugs, such as metformin and statins, which have shown promise in preclinical studies for their ability to disrupt these altered metabolic pathways. Conclusion Drug repurposing offers a promising strategy to overcome chemoresistance and improve patient outcomes. Future research should focus on unraveling the complex metabolic networks in OC to develop innovative, targeted therapies that can enhance treatment efficacy and patient survival.